2023
DOI: 10.1029/2023wr034484
|View full text |Cite
|
Sign up to set email alerts
|

The Music of Rivers: The Mathematics of Waves Reveals Global Structure and Drivers of Streamflow Regime

Abstract: River flow drives the structure and function of aquatic systems on sub-daily to decadal timescales, and sculpts landscapes on geological timescales from months to millennia (Fisher et al., 1998;Pinay et al., 2018;Tucker & Hancock, 2010). For people, variability in river flow regulates access to freshwater, with extreme flow events such as floods and droughts imposing immense personal and societal costs (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…Dams are one of the largest causes of stress, given their ubiquity (Belletti et al, 2020). However, a review of global flow regimes revealed that the effects of dams in large rivers were less influential than expected (Brown et al, 2023). Invasive species, pollutants, sedimentation, and many other stressors are involved and interacting, and when coupled with the changing baselines caused by climate change, the task of mitigating them is onerous (Ormerod et al, 2010).…”
Section: A General Approachmentioning
confidence: 99%
“…Dams are one of the largest causes of stress, given their ubiquity (Belletti et al, 2020). However, a review of global flow regimes revealed that the effects of dams in large rivers were less influential than expected (Brown et al, 2023). Invasive species, pollutants, sedimentation, and many other stressors are involved and interacting, and when coupled with the changing baselines caused by climate change, the task of mitigating them is onerous (Ormerod et al, 2010).…”
Section: A General Approachmentioning
confidence: 99%
“…This separation limits and fragments the understanding of catchment behaviour. Establishing physical controls on hydrological responses that act across multiple time scales could better unify hydrological theory, and lead to a more robust understanding of climate and landscape effects on hydrological response (Atkinson et al, 2002; Berghuijs et al, 2020; Brown et al, 2023; Rodriguez‐Iturbe et al, 1999; Sivapalan, 2006). From a more applied point of view, understanding seasonal and annual streamflow regimes is important for water resources management (Anghileri et al, 2016), agriculture (Letcher, 2004), and hydropower generation (Hamlet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously studying hydrological responses across multiple time scales (e.g., annual and seasonal) could be valuable as more data remain available, potentially reducing equifinality. In addition, controls on the long‐term water balance need to be consistent with shorter time‐scale behaviours, as long‐term water balances result inevitably from shorter time‐scale water balances (Brown et al, 2023).…”
Section: Introductionmentioning
confidence: 99%